Peran Kepala Sekolah, Guru, dan Alumni dalam Pengembangan Jiwa dan Kemampuan Kewirausahaan Siswa - Hapsari Dwi Marta Lita; Maisyaroh Maisyaroh; Juharyanto Juharyanto; Hapsari Dwi Marta Lita; Maisyaroh Maisyaroh (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2021)
Abstract: This study aims to describe: (1) the strategies of principals, teachers, and alumni in developing the entrepreneurial spirit of students; (2) strategies of principals, teachers, and alumni in developing student’s entrepreneurial abilities; (3) the role of principals and teachers in the implementation of a double track learning system; (4) alumni participation in the implementation of learning entrepreneurship practices for students; (5) constrains encountered in developing student’s entrepreneurial spirit and abilities; and (6) solutions to overcome the constraints to the development of entrepreneurial motivation and capacities. This research method used qualitative approach with a case study design data would collected through observation, interview, and documentation techniques. Based on the research data it can be concluded that principals, teachers, and alumni have several strategies in developing the spirit and entrepreneurial abilities of students. The strategy includes requiring students to go directly into school entrepreneurship activities, providing material related to entrepreneurship practices, implement literacy programs to develop, brainstorm, and create dream books. In addition, principals and teachers play a role as policy makers in the implementation of double track learning policies. Alumni also actively participate in the implementation of entrepreneurship practice learning. The constraints experienced by principals, teachers, and alumni in developing spirit and entrepreneurial abilities are the students have low awareness and confidence. These constraints can be overcome by providing motivation, assistance, and student insight. Abstrak: Penelitian ini bertujuan untuk mengetahui: (1) strategi kepala sekolah, guru, dan alumni dalam pengembangan jiwa kewirausahaan siswa; (2) strategi kepala sekolah, guru, dan alumni dalam pengembangan kemampuan kewirausahaan siswa; (3) peran kepala sekolah dan guru dalam penerapan sistem pembelajaran double track; (4) partisipasi alumni dalam pembelajaran praktik kewirausahaan siswa; (5) hambatan kepala sekolah, guru, dan alumni dalam mengembangkan jiwa dan kemampuan kewirausahaan siswa; dan (6) solusi kepala sekolah, guru, dan alumni dalam mengatasi hambatan pengembangan jiwa dan kemampuan kewirausahaan siswa. Metode penelitian ini menggunakan pendekatan kualitatif jenis studi kasus dengan teknik observasi, wawancara, dan dokumentasi. Berdasarkan data penelitian dapat disimpulkan bahwa kepala sekolah, guru, dan alumni memiliki beberapa strategi dalam pengembangan jiwa dan kemampuan kewirausahaan siswa. Strategi tersebut diantaranya adalah mewajibkan siswa terjun langsung dalam kegiatan kewirausahaan sekolah, pemberian materi yang berkaitan dengan praktik kewirausahaan, penerapan program literasi buku pengembangan, curah pendapat, dan pembuatan dream book. Selain itu kepala sekolah dan guru berperan sebagai pembuat kebijakan dan pelaksanaan kebijakan pembelajaran dengan sistem double track. Alumni juga berpartisipasi aktif dalam pelaksanaan pembelajaran praktik kewirausahaan siswa. Hambatan yang dialami kepala sekolah, guru, dan alumni dalam pengembangan jiwa dan kemampuan kewirausahaan siswa adalah kesadaran siswa dan tingkat kepercayaan diri siswa. Hambatan tersebut dapat diatasi dengan pemberian motivasi, pendampingan berkelanjutan, serta membuka pemikiran para siswa.